Análise molecular do gene CRTAP através da técnica de PCR-SSCP-sequenciamento em pacientes com osteogênese imperfeita do Espírito Santo - Almeida, Lorena Schneider (2013)
The Osteogenesis Imperfecta (OI) is a genetic disease characterized by structural defects of type I collagen protein or by reducing its biosynthesis causing decreased bone mass and predisposition to fractures and bone deformities. Approximately 90% of individuals with OI exhibit autosomal dominant inheritance caused by mutations in the genes COL1A1 and COL1A2. However, the number of genes linked to autosomal recessive forms of OI is increasing in the literature. The CRTAP gene was the second identified causing recessive inheritance OI. This gene has 6622 bp, seven exons and encodes a protein of 46.5 kDa. The CRTAP encoding the protein cartilage associated (CRTAP) which is part of the collagen 3-hydroxylation complex, responsible for post-translational modifications during the biosynthesis of collagen molecule. CRTAP mutations are related to severe and lethal form of the disease. The target of this research was evaluating the exons of CRTAP and its adjacent regions in OI patients from Espírito Santo thought the Single-Stranded Conformation Polymorphism (SSCP) screening of mutations and sequencing. We studied 24 patients with clinical diagnosis of OI from Hospital Infantil Nossa Senhora da Glória de Vitória, Brazil. The patients’ ages ranged from 2 to 16 years (median: 14.5). The sex proportion of the patients was 15 males and 9 females. Eleven patients have mild clinical symptoms of the disease, 5 show moderate symptoms and 9 were severe cases. The lethal OI cases were not obtained by methodological difficulties. We found the polymorphisms c.534C> T previously reported in exon 2 of the CRTAP gene in patients from sample. No pathogenic mutations were found in this study. The results of this study suggest that mutations in CRTAP are rare in ES population. These data may assist in developing more efficient methodological strategies for molecular diagnosis of OI.